Physiological and Psychological Responses during Exercise and Recovery in a Cold Environment Is Gender-Related Rather Than Fabric-Related - Cernych, Margarita; Baranauskiene, Neringa; Eimantas, Nerijus; Kamandulis, Sigitas; Daniuseviciute, Laura; Brazaitis, Marius (Frontiers in Psychology, 2017)
We evaluated gender-specific effects of two types of undergarments on exercise-induced physiological and psychological stress and subsequent recovery in cold conditions for male and female participants. Ten healthy men and eleven healthy women (25.0 ± 1.5 versus 23.4 ± 1.2 years old, respectively) completed the experimental session twice with two different types of undergarments: polyester or merino wool leggings and long-sleeve tops; specifically, merino fabric had greater thermal resistance and water absorbency, and less water vapour as well as air permeability than polyester. Experimental sessions involved performing 1 hour of exercise on a cycle ergometer at 8 °C ambient temperature and 55% relative humidity, holding at 70–80 revolutions per minute and 60% of each participant’s predetermined maximal power output (assessed by maximal oxygen uptake test), followed by 1 hour recovery in the same environment. Every 5 minutes during exercise and every 10 minutes during recovery, rectal temperature, heart rate, subjective ratings for thermal, shivering/sweating and clothing wetness sensations, and clothing next-to-skin and outer side surface temperature and humidity on the chest, back and thigh were recorded. All participants experienced high physiological stress (assessed by physiological strain index) during exercise. No significant gender differences were found in core temperature or heart rate changes during exercise, but women cooled down faster during recovery. Next-to-skin humidity was similar between genders and different garment sets during exercise and recovery, but such temperatures at the chest during exercise and at the thigh during exercise and recovery were lower in women with both sets of garments. Subjective thermal sensations were similar in all cases. In the last 20 min of cycling, women started to feel wetter than men (P < 0.05) for both garment sets. Shivering was reported as stronger in women in the last 10 minutes of recovery. Most of the changes in the garment microclimates during exercise and recovery in the cold were associated with gender-related differences rather than with fabric-related differences.